Collaboration, competition and strategic costing: Knowing when to start learning - Bhimani, A.; Frantz, P.; Gulamhussen, M. A.; Ncube, M. (International Journal of Accounting, Auditing and Performance Evaluation, 2008)
Many companies confronted with 'make or buy' decisions adopt the mid-way option of engaging in collaborative relationships (CRs) with suppliers rather than in internal production or the purchasing of parts through a process of competitive bidding. Engaging in CRs requires evaluations of when to enter such relationships and when to abandon them. Traditional incremental cost analysis does not readily allow such analysis for the establishment of supplier networks and relationships. This paper develops a real options-based model that focuses on the cost implications of learning curves and timing concerns. It provides an optimal timing valuation approach to establishing/abandoning a CR that incorporates differential learning rate payoffs and that assesses the contingencies embedded in a CR. A standard illustration of the application of the model is provided.